Flexion-relaxation ratio in computer workers with and without chronic neck pain. - Pinheiro, Carina Ferreira; Santos, Marina Foresti dos; Chaves, Thais Cristina; dos Santos, Marina Foresti (Journal of Electromyography & Kinesiology, 2016)
This study evaluated the flexion-relaxation phenomenon (FRP) and flexion-relaxation ratios (FR-ratios) using surface electromyography (sEMG) of the cervical extensor muscles of computer workers with and without chronic neck pain, as well as of healthy subjects who were not computer users. This study comprised 60 subjects 20-45years of age, of which 20 were computer workers with chronic neck pain (CPG), 20 were computer workers without neck pain (NPG), and 20 were control individuals who do not use computers for work and use them less than 4h/day for other purposes (CG). FRP and FR-ratios were analyzed using sEMG of the cervical extensors. Analysis of FR-ratios showed smaller values in the semispinalis capitis muscles of the two groups of workers compared to the control group. The reference FR-ratio (flexion relaxation ratio [FRR], defined as the maximum activity in 1s of the re-extension/full flexion sEMG activity) was significantly higher in the computer workers with neck pain compared to the CG (CPG: 3.10, 95% confidence interval [CI95%] 2.50-3.70; NPG: 2.33, CI95% 1.93-2.74; CG: 1.99, CI95% 1.81-2.17; p<0.001). The FR-ratios and FRR of sEMG in this study suggested that computer use could increase recruitment of the semispinalis capitis during neck extension (concentric and eccentric phases), which could explain our results. These results also suggest that the FR-ratios of the semispinalis may be a potential functional predictive neuromuscular marker of asymptomatic neck musculoskeletal disorders since even asymptomatic computer workers showed altered values. On the other hand, the FRR values of the semispinalis capitis demonstrated a good discriminative ability to detect neck pain, and such results suggested that each FR-ratio could have a different application.